A Monte Carlo-based Evaluation of Fishery Management Strategies for Lizardfish (Saurida undosquamis) in the Gulf of Suez, Red Sea (Global Journal of Science Frontier Research, 2023)
Lizardfish Saurida undosquamis is one of the most popular fishes inhabiting the Red Sea and migrated then widely distributed in the Mediterranean Sea Monte Carlo method-based Surplus Production Model CMSY was used to predict the biological reference points PRBs for S unodsquamis using catch and catch per unit of effort time series data 1980-2021 The Biological Reference Points for S unodsquamis are MSY 1 4 1000ton B BMSY 0 629 Exploitation F FMSY 1 29 Carrying Capacity k 18 2 1000ton The intrinsic growth rate of the fish population r 0 304 y-1 Such information constructs the base to set up a reliable strategy to rebuild the stock and avoid the management side effects on the community of the fishermen
Keywords: stock status; biological reference points; Saurida undosquamis; CMSY; Gulf of suez